Appropriate Application of Sawob M-Banking Technology To Develop Waste Bank Management in Bae Village - Noor Romadlon, Farid; Ratna Wijayani, Dianing; Agus Triyanto, Wiwit (Devotion : Journal of Community Service, 2022)
Garbage is a consequence of human activities. Along with the increasing population and current economic growth, waste management in the community creates uncontrolable problems. Based on this, one of the Community Service Program teams at Universitas Muria Kudus established a partnership with the Tanjung Seto Youth Organization in Bae village to help manage waste in the area. The main and urgent problem from partners that needs to be resolved is the operational activities of the waste bank. These problems include the socialization of waste bank activities, technical transactions, and circulation of waste bank savings money so that it is more efficient, effective, and practical and more citizens participate. The objective of this program is to assist the operational activities of the waste bank by using an android-based application named SAWOB M-Banking to support the process and mechanism of the Waste Bank activities. The method used to implement the solution is mentoring and knowledge transfer. Identifying needs will be accomplished through data collection on waste bank schedules, the number of waste bank clients, waste categories and price values, and customer savings data. Furthermore, processing the obtained data then making the SAWOB M-Banking application. The SAWOB M-Banking application has been socialized to customers gradually and tested for 10 customers in waste bank activities. After being simulated, the SAWOB M-Banking application has been used for all waste bank customers in Bae village.